Colorimetric Kit for Rapid Porcine Circovirus 2 (PCV-2) Diagnosis - Basso, Caroline Rodrigues [UNESP] (2022)
The aim of the current study is to present a low-cost and easy-to-interpret colorimetric kit used to diagnose porcine circovirus 2 (PCV-2) to the naked eye, without any specific equipment. The aforementioned kit used as base hybrid nanoparticles resulting from the merge of surface active maghemite nanoparticles and gold nanoparticles, based on the deposition of specific PCV-2 antibodies on their surface through covalent bonds. In total, 10 negative and 40 positive samples (≥102 DNA copies/µL of serum) confirmed by qPCR technique were tested. PCV-1 virus, adenovirus, and parvovirus samples were tested as interferents to rule out likely false-positive results. Positive samples showed purple color when they were added to the complex, whereas negative samples showed red color; they were visible to the naked eye. The entire color-change process took place approximately 1 min after the analyzed samples were added to the complex. They were tested at different dilutions, namely pure, 1:10, 1:100, 1:1000, and 1:10,000. Localized surface plasmon resonance (LSPR) and transmission electron microscopy (TEM) images were generated to validate the experiment. This new real-time PCV-2 diagnostic methodology emerged as simple and economic alternative to traditional tests since the final price of the kit is USD 4.00.